Penetapan Kadar Zink Ikan Lele (Clarias batrachus) dari Pasar Sei Sikambing secara Spektrofotometri Sinar Tampak - Muhammad Gunawan; Rahmad Hidayat (Yayasan Penelitian dan Inovasi Sumatera, 2021)
Clarias batrachus is one of the commercially cultivated freshwater fish species in Indonesia, especially in North Sumatra. Nutrinya content of protein, fat, minerals, carbohydrates, and water. Minerals play an important role in metabolic processes that ensure the maintenance of body functions at the cellular, tissue and organ levels. The research was aimed at determining the zinc content of raw, steamed, grilled, and fried catfish by using visible light spectrophotometry method after destruction and adding alkaline dithizone solution. Clarias batrachus samples were taken purposively from the traditional market of Sei Sikambing Medan. Method validation includes accuracy, precision, and sensitivity. The results show that it is accurate with accuracy, precision, limit of detection and quantitation of 99.95% each; 1.06%; 0.620 g/ml; 2.066 g/ml. ANOVA test showed no significant difference in zinc content of raw, steamed, grilled, and fried catfish.